(untitled) (Global Journal of Human-Social Science, 2021)
The COVID-19 pandemic has set new challenges before the world in all areas including, education, and India is not an exception. The elementary, secondary and higher education system of our country is severely affected with this deadly disease. As such, the schools, colleges and universities have suspended their offline classes throughout the country since March last week of 2020. Amidst these challenges, it has also opened up new opportunities for the teachers, educators, and technocrats, etc. to use online virtual learning strategies for imparting learning experiences to students across the world. Thus, techno-pedagogy is the need of the hour in India and especially in Higher Education. However, the nation is gradually moving towards normalcy, and offline classes have been started by some of the states. Hence, it was necessary to assess how effective online teaching, learning and evaluation in the context of offline teaching, learning and examination. The present paper highlights the views of the undergraduate students on the feasibility of online teaching, learning and examination in the state of Arunachal Pradesh.